Deep intact proteoform quantification of low-microgram-scale proteome by tandem mass tag labeling and online 2D high-pH/low-pH RPLC top-down analysis - Yanting Guo; Trishika Chowdhury; Walter P. Galie; Kellye A. Cupp-Sutton; Zhitao Zhao; Ashlyn Solenberger; Dahang Yu; Si Wu (Analytica Chimica Acta, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Single atom anchored covalent organic framework assisted with machine learning for high-throughput pesticides discrimination - Rui Bai; Nan Chen; Chenchen Gong; Yanting Liu; Shasha Lu; Jianyu Yang; Qiulin Li; Yu Gu; Changming Li; Chunxian Guo (Chemical Engineering Journal, 2026)

Insights into distinct biocarbon assembly and graphitization derived from large-scale bioresource by integrating machine learning with Raman and XRD spectroscopic profiling - Junsheng Yu; Jing Hong; Yujia Fang; Jiacheng Kang; Zongtai Tang; Lei Zhu; Bing Gao; Ling Luo; Dan Sun; Yanting Wang; Liangcai Peng; Hua Yu (Bioresource Technology, 2026)

Effects of the Biosurfactant Rhamnolipid on the hygroscopicity and cloud condensation nuclei activity (CCN) of ammonium sulfate aerosols - Wenxu Fang; Zhijun Wu; Taomou Zong; Yanting Qiu; Xiangxinyue Meng; Jingchuan Chen; Zeyu Feng; Junrui Wang; Linghan Zeng; Zheng Chen; Zirui Zhang; Yu Xie; et al. (Atmospheric Research, 2026)

Revealing nonlinear impact disparities of vegetation-building configurations on carbon sequestration efficiency through representation learning - Mengqing Yu; Yanting Shen; Jiahong Ye; Chenfeng Hou; Mingyi He; Chenyu Huang; Jiawei Yao (Urban Forestry & Urban Greening, 2026)

Quantifying the contribution of reactive nitrogen loss through anaerobic ammonium oxidation in global wetlands and oxygen minimum zones - Bangrui Lan; Shuci Liu; Shanyun Wang; Yanting Zhang; Longbin Yu; Chunlei Liu; Guibing Zhu (Journal of Environmental Sciences, 2026)

Magnetic resonance imaging for rapid, noninvasive and accurate assessment of ovarian maturation in live Channa argus (Cantor, 1842) - Wenqian Sun; Weiyin Vivian Liu; Xingyu Chen; Guangcan Lin; Hao Li; Yanting Song; Chengdong Peng; Wen Xiong; Yu Peng; Shangong Wu; Shouqi Xie; Sovan Lek; et al. (Aquaculture, 2026)

Dynamic traffic encountering scenario generation for testing of ship collision avoidance algorithm - Weiqiang Wang; Kezhong Liu; Lijia Chen; Yuerong Yu; Yanting Tong; Xiaolie Wu; Zhitao Yuan (Ocean Engineering, 2026)

Diesel exhaust induces hepatic steatosis by activating the aryl hydrocarbon receptor/CD36 pathway - Qian Song; Xueying Zhang; Yanting Li; Zixuan Liang; Ao Han; Xiaoran Wei; Xiaowen Tang; Juntong Wei; Wei Han; Shanfa Yu; Hongna Zhang; Yuxin Zheng (Journal of Hazardous Materials, 2026)

Synergistic construction of lignin-modified multifunctional hydrogels via dynamic ionic networks and nanoclay physical reinforcement: From superior mechanical properties to fine tactile sensing - Yongjian Zhang; Yi Zhang; Zuochao Zhu; Chaofei Guo; Yanting Chen; Zien Xu; Xiao Yu; Minghui Li; Yuxuan Wang; Xuejuan Yang; Xiping Luo (Chemical Engineering Journal, 2026)

Exploring the mechanisms of torularhodin in alleviating diabetic kidney disease: a microbiome and metabolomics approach through the gut-kidney axis - Wenlong Deng; Yi Guo; Qigui Mo; Jiaqi Liu; Yanting Su; Zhihao Wei; Runtao Ma; Jiaqi Chen; Yue Song; Tianqi Chen; Peng Wang; Wei Yu; et al. (Food Research International, 2025)

Metabolic network remodeling through PxJHE modulates temperature adaptation in a cosmopolitan insect - Gaoke Lei; Huiling Zhou; Guangyu Yu; Xin Miao; Yu Zhang; Zongyao Ma; Yating Duan; Yanting Chen; Fengluan Yao; Liette Vasseur; Shijun You (Insect Biochemistry and Molecular Biology, 2025)

Protocol for the purification and culture of primary retinal ganglion cells and development of common pathological models - Xiaoding Shui; Yan Wang; Yu Luo; Xiaoyu Liang; Tao Chen; Yanting Xia; Qiping Wei; Liang Liao (Journal of Molecular Histology, 2025)

Halomonas fermentation promoted the biotransformation of active substances from Dictyophora indusiata pileus and the enhancement of antioxidant capacity - Xueying Zheng; Ying He; Lei Ma; Yanting Sun; Jiazi Yu; Zeguo Feng; Censhu Li; Jiaru Jiang; Xiaoni Zhang; Liguo Qin; Dan Tan; Yali Zhang (Food Bioscience, 2025)

A large-scale integrated transcriptomic atlas for soybean organ development - Jingwei Fan; Yanting Shen; Chuan Chen; Xi Chen; Xiaoyue Yang; Haixia Liu; Ruiying Chen; Shulin Liu; Bohan Zhang; Min Zhang; Guoan Zhou; Yu Wang; et al. (Molecular Plant, 2025)

Vibroacoustic Response of a Disc-Type Underwater Glider During Its Entry into Water - Zhaocheng Sun; Yanting Yu; Dong Li; Chuanlin He; Yue Zhang (Journal of Marine Science and Engineering, 2025)
Underwater gliders are extensively employed in oceanographic observation and detection. The structural characteristics of thin-wall shells are more susceptible to vibrations from internal mechanical components; this noise emission becomes more complex with the presence of water surfaces. The finite element method (FEM) is introduced to discuss the dynamic performance of cylindrical shells with different lengths. The acoustic-structure coupling, together with the effect of the water surface, is validated by comparisons with experimental or analytical solutions under three cases: half-filled, half-submerged, and partially submerged in fluid. Compared to the verification result, the relative error of the eigenfrequency derived from the numerical result is less than 3%, and then the mesh division and boundary conditions are adjusted to calculate the vibroacoustic response of a disc-type glider. During its water entry process, there are six distinct bright curves in frequency–depth spectra of sound pressure radiated from a partially immersed disc-type glider. The first curve is continuous, while the remaining five curves display discontinuities around a region where the geometric curvature changes gradually. As the submerged depth increases, this causes a shift in the resonance frequencies, evidenced by the curves transitioning from higher to lower frequencies.

The coupling development of energy-economy-environment from the perspective of rural households: Insights into preventing returning to poverty - Xin Cheng; Ziyi Yu; Jingyue Gao; Li Chen; Yaru Jiang; Yanting Liu; Yan Dai; Jia Chen; Chaofan Wang; Chenfeng Wang; Yongjie Zheng; Huimin Zhou; et al. (Land Use Policy, 2025)

Exploring the Correlation Between Varied Serum Iodine Nutritional Levels and Anti-Thyroglobulin Antibodies - Qiuyi Song; Tingting Xu; Yu Wang; Hongyan Wei; Feng Tan; Yanting Chen; Fang Fang; Tingkai Cui; Ziyun Pan; Xiaohui Guo; Wen Chen; Jun Shen; et al. (Biological Trace Element Research, 2025)

Analyzing inequities in vegetation cooling services along the urban-rural gradient using the LAI-integrated InVEST urban cooling model - Hailian Lan; Yanting Zhang; Yinan Yang; Xian Zhao; Tao Yu; Xiangyun Li; Benyao Wang; Yujing Xie (Urban Forestry & Urban Greening, 2025)

Distinct lignocelluloses of plant evolution are optimally selective for complete biomass saccharification and upgrading Cd2+/Pb2+ and dye adsorption via desired biosorbent assembly - Huiyi Zhang; Yongtai Wang; Hao Peng; Boyang He; Yunong Li; Hailang Wang; Zhen Hu; Hua Yu; Yanting Wang; Mengzhou Zhou; Liangcai Peng; Miao Wang (Bioresource Technology, 2025)

Transcriptional and functional analysis of epilactose transport and catabolism in the probiotic Ligilactobacillus salivarius ZL6 - Yuwei Zhang; Xiaoqing Xu; Qing Peng; Yanting Tian; Xiaoming Chen; Dandan Tian; Lan Ma; Yuxin Gong; Yu Qiao; Bo Shi (Food Bioscience, 2025)

Insights into contrastive cellulose nanofibrils assembly and nanocrystals catalysis from dual regulations of plant cell walls - Yuanhang Ai; Hailang Wang; Peng Liu; Hua Yu; Mengdan Sun; Ran Zhang; Jingfeng Tang; Yanting Wang; Shengqiu Feng; Liangcai Peng (Science Bulletin, 2024)

Is ignorance bliss? Evaluating information awareness and life satisfaction through the lens of perceived air pollution: The case of Beijing, China - Xiaohan Yu; Yanting Fan; Joon Sik Kim; Hyungchul Chung; Alex Lord; Richard Dunning (Journal of Environmental Management, 2024)

Weak magnetic field promotes denitrification by stimulating ferromagnetic ion-containing metalloprotein expression - Yuan Lin; Yanting Chen; Haiyue Wang; Yuexin Yu; Yanru Wang; Sijia Ma; Laichun Wang; Hongqiang Ren; Ke Xu (Water Research, 2024)

Revolutionizing marine Protection: Innovative designs for In-Situ applicable underwater antifouling superoleophobic coatings - Zhaoji Xia; Xiubin Xu; Xusheng Jiang; Jianmin He; Yanting Chen; Danfeng Yu; Zhenyu Wang; Xu Wu; Hongbo Zeng (Chemical Engineering Journal, 2024)

Insights in to iron-based nanoparticles (hematite and magnetite) improving the maize growth (Zea mays L.) and iron nutrition with low environmental impacts - Nauman Yousaf; Muhammad Fahad Sardar; Muhammad Ishfaq; Baogang Yu; Yanting Zhong; Faisal Zaman; Fusuo Zhang; Chunqin Zou (Chemosphere, 2024)

Long-term investigation of spatial–temporal variations, risk assessments, and controlling factors of persistent organic pollutants (HCHs, DDTs, and PAHs) and heavy metals in coastal regions along the Chinese Bohai Sea - Yanting Su; Wanguan Wang; Yueyue Su; Xiaoxuan Wang; Haitao Zhao; Zhunjie Li; You Yu (Frontiers in Marine Science, 2024)
Persistent organic pollutants (POPs) and heavy metals in marine systems have been given more and more attention due to their high toxicity and bioaccumulation capacity. After discharging into the marine systems, large proportions of POPs and heavy metals are likely to remain in coastal seas, causing serious contamination and high ecological risks. However, the lack of systematic studies restricts our understanding of POP and heavy metal cycling in coastal regions. Herein, the coastal regions along the Chinese Bohai Sea (an important fishing and typically polluted area) were chosen to establish a study model for investigating long-term spatial–temporal variations, risk assessments, and controlling factors of hexachlorocyclohexanes (HCHs), dichlorodiphenyltrichloroethanes (DDTs), polycyclic aromatic hydrocarbons (PAHs), and heavy metals in coastal regions. The results showed that concentrations of HCHs, DDTs, and PAHs in sediment, and contents of heavy metals in seawater and sediment were higher than those in other coastal regions during 2015–2018 and that concentrations of As and Cu in approximately 95% and 20% of sampled organisms exceeded maximum permissible levels recommended by China and the WHO, respectively. The significantly temporal variations in HCH and PAH concentrations were indicative of increasing POP pollution, and no significantly temporal variations in most heavy metal concentrations were found. Meanwhile, the higher concentrations of POPs and heavy metals were mainly located in estuaries and other nearshore areas. The geo-accumulation index (I geo ), potential ecological risk index (PERI), and provisional tolerable daily intake (PTDI) showed that As, Cd and Hg should be listed as the primary heavy metal pollutants in sediment; higher dietary risk was posed by As through seafood consumption; the dietary risks posed by HCHs, DDTs, and PAHs were lower. Finally, the results of multiple regression, Pearson’s, and cluster analyses indicated that anthropogenic activities (e.g., industrial and agricultural discharges, and riverine input) played important roles in controlling HCH, DDT, PAH, and heavy metal distributions in coastal regions along the Chinese Bohai Sea. The outcomes of this study are expected to shed new light on an improved understanding of POP and heavy metal cycling and provide a scientific basis for contamination control in coastal systems.

Governance effects of pollution reduction and carbon mitigation of carbon emission trading policy in China - Xin Cheng; Ziyi Yu; Jingyue Gao; Yanting Liu; Shiwei Jiang (Environmental Research, 2024)

Antibacterial oxygen-sulfur terminal polymers from a facile initiator-strategy - Yanting Chen; Xiubin Xu; Canwen Yu; Yang Xue; Hao Wang; Yaozhi Wang; Minghui Xie; Xusheng Jiang; Jing Lyu; Wenxin Wang; Xu Wu (Chemical Engineering Journal, 2024)

Cationic cellulose nanofiber solid electrolytes: A pathway to high lithium-ion migration and polysulfide adsorption for lithium-sulfur batteries - Chenhao Ji; Shuanglin Wu; Feng Tang; Yanting Yu; Fenglin Hung; Qufu Wei (Carbohydrate Polymers, 2024)

How to restore the livelihood resilience of the rural vulnerable? Evidence from 1,356 households in rural China - Xin Cheng; Ziyi Yu; Jingyue Gao; Yanting Liu; Yan Dai; Jia Chen; Guangjie Liu; Zhiju Xie (Environment, Development and Sustainability, 2024)

Heavy metal induced shifts in microbial community composition and interactions with dissolved organic matter in coastal sediments - Yu Wang; Yuxing Hu; Yanting Liu; Qi Chen; Jinxin Xu; Fei Zhang; Jinhua Mao; Quan Shi; Chen He; Ruanhong Cai; Christian Lønborg; Lihua Liu; et al. (Science of The Total Environment, 2024)

Has the Establishment of a FTZ Promoted the High-quality Development of the Pharmaceutical Manufacturing Industry?——Quasi Natural Experiments Based on the Establishment of the First Three Batches of Pilot FTZ - Dingxiang Fan; Mengjie He; Yanting Yu; Yuguo Liu (Journal of Pharmaceutical Innovation, 2024)

Organelle-like water-borne curcumin nanoparticles with smart fluorescence for anti-counterfeiting and food quality monitoring - Yanting Chen; Hao Wang; Xiubin Xu; Hui Ye; Chuanghong Xiao; Jian Bai; Minghui Xie; Siti Chen; Insu Jeon; Danfeng Yu; Ting Chen; Xu Wu (Chemical Engineering Journal, 2024)

Nutrient enrichment driven by canopy rainfall redistribution: Mechanism, quantification, and pattern - Chuan Yuan; Xiaoping Yue; Yafeng Zhang; Yu Zhang; Yanting Hu; Qiang Tang; Li Guo; Shuai Wang; Xingwu Duan; Wenhua Xiang; Xiaohua Wei; Xiaoyan Li (Science China Earth Sciences, 2024)

Enhanced peroxymonosulfate (PMS) activation process mediated by vanadium modified CoO catalyst for rapid degradation of organic pollutants: Insights into the role of V - Yanting Jiang; Xin Weng; Yihui Hu; Yuancai Lv; Zhendong Yu; Yifan Liu; Xiaojuan Li; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2024)

Accumulation and composition characteristics of organic phosphorus in sediments from the Yangtze River–connected lakes, China - YanTing Yan; Dongzheng Liu; WenJun Zhong; Zhaokui Ni; Yu Li; Shengrui Wang (Journal of Soils and Sediments, 2024)

The environmental risks of antiviral drug arbidol in eutrophic lake: Interactions with Microcystis aeruginosa - Ziwei Guo; Huan He; Gui Yang; Kunqian Liu; Yanting Xi; Zihui Li; Yu Luo; Zhicheng Liao; Guohua Dao; Xiaomin Ren; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2024)

Adding a basis for sustainable poverty monitoring: The indicator systems and multi-source data of multi-dimensional poverty measurement - Xin Cheng; Yanting Liu; Ziyi Yu; Jingyue Gao; Yan Dai; Jia Chen; Yue Liu; Chaofan Wang; Chuanmin Shuai; Wenjing Li; Zhiju Xie (Environmental Development, 2024)

Different ligand functionalized bimetallic (Zr/Ce)UiO-66 as a support for immobilization of phosphotungstic acid with enhanced activity for the esterification of fatty acids - Qiuyun Zhang; Yaping Wu; Xingyue Hong; Zhenying Li; Yanting Lei; Rongfei Yu; Taoli Deng; Yutao Zhang; Peihua Ma (Sustainable Chemistry and Pharmacy, 2024)

Efficient data-driven prediction of household carbon footprint in China with limited features - Na An; Chenyu Huang; Yanting Shen; Jinyu Wang; Zhongqi Yu; Jiayan Fu; Xiao Liu; Jiawei Yao (Energy Policy, 2024)

Quantifying threshold and scale response of urban air and surface temperature to surrounding landscapes under extreme heat - Xinyu Bai; Zhaowu Yu; Benyao Wang; Yanting Zhang; Siqi Zhou; Xiaohan Sha; Siheng Li; Xihan Yao; Xiaolei Geng (Building and Environment, 2024)

A comprehensive study on the performance and mechanism of microplastics removal by enhanced coagulation methods - Zhiqin Li; Yujian Zhang; Xin Wei; Lupeng Huang; Jing Zhang; Yan Wu; Yanting Zhang; Yu Xiang (Journal of Water Process Engineering, 2023)

Mesopore-dominated porous carbon derived from confinement-region activation strategy toward high capacitive desalination performance - Bofeng Li; Zhihua Xiao; Yanting Cao; Zhiqing Yu; Yankun Sun; Zechen Li; Yuxian Wang; Zhenfei Gao; Chunming Xu (Fuel, 2023)

Diesel exhaust particles exposure induces liver dysfunction: Exploring predictive potential of human circulating microRNAs signature relevant to liver injury risk - Lin Xu; Yanting Li; Wanli Ma; Xueying Sun; Rongrong Fan; Yuan Jin; Ningning Chen; Xiaoxiao Zhu; Huan Guo; Kunming Zhao; Jiao Luo; Chuanhai Li; et al. (Journal of Hazardous Materials, 2023)

ROS production upon groundwater oxygenation: Implications of oxidative capacity during groundwater abstraction and discharging - Yanting Zhang; Na Zhang; Chenglong Yu; Hui Liu; Songhu Yuan (Journal of Hydrology, 2023)

Rapid degradation of PFOA by the activated peroxymono-sulfate with FeCo/MoS2 catalyst - Yuancai Lv; Shiyu He; Shuting Liu; Zhendong Yu; Yanting Jiang; Yihui Hu; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2023)

Corrigendum to “Limited hydrolysis of glycosylated whey protein isolate ameliorates the oxidative and physical stabilities of conjugated linoleic acid oil-in-water emulsions” [Food Chem. 362 (2021)130212] - Meng Li; Rui Yu; Runxiao Fu; Yanting He; Zhanmei Jiang; Juncai Hou (Food Chemistry, 2023)

Effect of morphology and simultaneous sulfation on Fe doped CeO2 for selective catalytic reduction of NO with NH3 - Jinxiu Wang; Yuqiu Liu; Xianfang Yi; Yanting Chen; Yanke Yu; Jinsheng Chen (Fuel, 2023)

Quinoxaline-Based Donor-Acceptor conjugated polymers for nonvolatile ternary memory devices - Zhaohua He; Xudong Chen; Haifeng Yu; Yanting Du; Meng Gao; Shuhong Wang; Cheng Wang (Chemical Engineering Journal, 2023)

Anion-exchange assisted sequential deposition for stable and efficient FAPbI3-based perovskite solar cells - Xinning Jiao; Wei-Min Gu; Yanting Xu; Ke-Jian Jiang; Guanghui Yu; Qing-Wu Zhang; Cai-Yan Gao; Cai-Ming Liu; Xin-Heng Fan; Lian-Ming Yang; Yanlin Song (Chemical Engineering Journal, 2023)

Circulating expression and clinical significance of LncRNA ANRIL in diabetic kidney disease - Yanting Zhu; Lixia Dai; Xiangyou Yu; Xintian Chen; Zhenjiang Li; Yan Sun; Yan Liang; Bing Wu; Qiong Wang; Xiaoming Wang (Molecular Biology Reports, 2022)
Background Long noncoding RNA ANRIL has been found to be involved in the pathogenesis of diabetic kidney disease (DKD) and is expected to be a new target for prevention of DKD. However, the circulating expression and clinical significance of ANRIL in DKD patients is uncertain. This study aims to explore this issue. Methods The study consisted of 20 healthy controls, 22 T2DM patients (normalbuminuria) and 66 DKD patients (grouped as follows: microalbuminuria, n = 23; macroalbuminuria, n = 22 and renal dysfunction, n = 21). The expressions of ANRIL in peripheral whole blood of all participants were measured by RT-qPCR. Results The expression of ANRIL was significantly up-regulated in DKD patients (microalbuminuria, macroalbuminuria and renal dysfunction groups) than that in healthy control group. ANRIL was also over-expressed in macroalbuminuria and renal dysfunction groups in comparison with normalbuminuria group. ANRIL expression was positively correlated with Scr, BUN, CysC, urine β2-MG and urine α1-MG; while negatively correlated with eGFR in DKD patients. In addition, ANRIL was the risk factor for DKD with OR value of 1.681. The AUC of ANRIL in identifying DKD was 0.922, and the sensitivity and specificity of DKD diagnosis were 83.3% and 90.5%, respectively. Conclusion Our results indicated that highly expressed ANRIL in peripheral blood is associated with progression of DKD. Circulating ANRIL is an independent risk factor of DKD and has a highly predictive value in identifying DKD.

The Biocompatibility of Multi-Source Stem Cells and Gelatin-Carboxymethyl Chitosan-Sodium Alginate Hybrid Biomaterials - Xinzhe Wang; Siqi Li; Honglian Yu; Jianzhi Lv; Minglun Fan; Ximing Wang; Xin Wang; Yanting Liang; Lingna Mao; Zhankui Zhao (Tissue Engineering and Regenerative Medicine, 2022)

Microbiome of juvenile corals in the outer reef slope and lagoon of the South China Sea: insight into coral acclimatization to extreme thermal environments - Zhenjun Qin; Kefu Yu; Shuchang Chen; Biao Chen; Jiayuan Liang; Qiucui Yao; Xiaopeng Yu; Zhiheng Liao; Chuanqi Deng; Yanting Liang (Environmental Microbiology, 2021)
Summary Environmental conditions between the outer reef slope (ORS) and lagoon in tropical atolls are significantly different, but the variations of juvenile coral‐microbiomes in the two environments and their relationship with coral thermal acclimatization are poorly understood. We explored this issue based on local water conditions and the microbiome of juvenile corals in the ORS and lagoon in the central South China Sea. Coral‐symbiotic Symbiodiniaceae showed significant differences among coral species; Pocillopora verrucosa and Pachyseris rugosa in the ORS, and Acropora formosa in the lagoon were dominated by Durusdinium , but other corals were dominated by Cladocopium . Although A. formosa in the ORS were dominated by Cladocopium (C3u), they were dominated by Durusdinium (D1/D1a) and Cladocopium (C50) in the lagoon. Other coral species were both dominated by Cladocopium in the lagoon and ORS. The relative abundance of bacteria in the Deinococcus–Thermus was generally higher in the lagoon corals than in the ORS corals. Our study indicates that P. verrucosa , P. rugosa and Porites lutea may have high thermal tolerance based on the relatively high abundance of heat‐tolerant Durusdinium and Thermus scotoductus . Likewise, A. formosa in the lagoon may acclimatize to the thermal environment based on a high relative abundance of heat‐tolerant Durusdinium .

Top‐down controls on nutrient cycling and population dynamics in a model estuarine photoautotroph–heterotroph co‐culture system - Qiang Zheng; Wenxin Lin; Yu Wang; Dapeng Xu; Yanting Liu; Nianzhi Jiao (Molecular Ecology, 2021)
Viral lysis and protistan grazing are thought to be the major processes leading to microbial mortality in aquatic environments and thus regulate community diversity and biogeochemical cycling characteristics. Here, we studied nutrient cycling and bacterial responses to cyanophage‐mediated photoautotroph lysis and ciliate predation in a model Synechococcus –heterotroph co‐culture system. Both viral lysis and Euplotes grazing facilitated the transformation of organic carbon from biomass to dissolved organic matter with convention efficiencies of 20%–26%. The accumulation of ammonium after the addition of phages and ciliates suggested the importance of recycled NH 4 + occurred in the interactions between Synechococcus growth and heterotrophic bacterial metabolism of photosynthate. The slower efficiency of P mineralization compared to N (primarily ammonium) indicated that P‐containing organic matter was primarily integrated into bacterial biomass rather than being remineralized into inorganic phosphate under C‐rich conditions. In the cyanophage addition treatment, both Fluviicola and Alteromonas exhibited rapid positive responses to Synechococcus lysing, while Marivita exhibited an apparent negative response. Further, the addition of Euplotes altered the incubation system from a Synechococcus ‐driven phycosphere to a ciliate‐remodelled zoosphere that primarily constituted grazing‐resistant bacteria and Euplotes symbionts. Top‐down controls increased co‐culture system diversity and resulted in a preference for free‐living lifestyles of dominant populations, which was accompanied by the transfer of matter and energy. Our results indicate top‐down control was particularly important for organic matter redistribution and inorganic nutrient regeneration between photoautotrophs and heterotrophs, and altered bacterial lifestyles. This study consequently sheds light on marine biogeochemical cycling and the interaction networks within these dynamic ecosystems.

Numerical Study on the Natural Convection of Air in a Cubic Cavity Subjected to a Yawing Motion - Guojun Yu; Lizhi Zhang; Sheng Jia; Yanting Geng; Jie Liu (Journal of Marine Science and Engineering, 2019)
Natural convections subjected to multi-Degree of Freedom (DoF) motion are much more complex than those in static case, and those subjected to yawing motion are the simplest and ideal case for investigating their characteristics due to less interactive parameters. In this paper, the characteristic of natural convection under yawing motion was studied systematically to clarify the interaction between yawing motion and thermal-dynamic behavior. First of all, the mathematical model was established in a non-inertial coordinate system, and the dimensionless governing equations were derived. Subsequently, the governing equations were discretized in the framework of the finite volume method, and a computer code was developed and validated. After that, the natural convection under yawing motion was calculated with different combinations of dimensionless parameters, and the influence of rotation frequency and amplitude on heat and mass transfer was investigated. It was found that the yawing motion plays a notable role in flow and heat transfer, depending on the relative magnitudes of rotation-induced velocity and buoyancy-induced velocity: At a lower Rayleigh number of 104, the Nusselt number on hot boundary is enhanced by approximately 25% when the rotation period is changed from 12 s to 2 s; while the changing in rotation period from 12 s to 2 s did not induce obvious difference in hot-boundary Nusselt number for a higher Rayleigh number of 105. It is concluded that the vertical-axis harmonic rotation enhances heat transfer if the rotation-induced velocity dominates the flow. The clarification of natural convection characteristic in yawing motion provides convenience for analyzing that in other multi-DoF systems.

Numerical Investigation into the Two-Phase Convective Heat Transfer within the Hold of an Oil Tanker Subjected to a Rolling Motion - Guojun Yu; Sheng Jia; Yanting Geng (Journal of Marine Science and Engineering, 2019)
A crude oil tanker usually encounters a rolling motion during sea transportation, which leads to rotational movement and sometimes a sloshing of the liquid hold. This rolling-induced body motion seriously affects the thermal and hydraulic behavior of the liquid hold, which then affects the heating process and heat preservation of the tanker. Clarification of the involved thermal and hydraulic characteristics is the basic requirement for establishment of a scientific heating scheme and heat preservation method. A two-phase 3D model considering the free liquid surface and non-Newtonian behavior of the fluid was established for the thermal calculation of the liquid holds in oil tankers. The thermal and hydraulic characteristics of the liquid hold were investigated under different combinations of dimensionless parameters, and the combined effect of rolling and fluid non-Newtonian behavior was investigated. It was found that rolling intensifies the heat transfer based on the combination of the Richardson number ( R i ) and the rotation-strength number ( ω * ), and non-Newtonian behavior of the fluid effectively affects the heat transfer in a rolling motion. This research is expected to provide a reference for design and optimization of the heating and heat preservation method for oil tanker operation.

Identification and association of novel lncRNA pouMU1 gene mutations with chicken performance traits - Tuanhui Ren; Yanting Zhou; Yu Zhou; Weihua Tian; Zhenzhen Gu; Song Zhao; Yadi Chen; Ruili Han; Xiaojun Liu; Xiangtao Kang; Zhuanjian Li (Journal of Genetics, 2017)

MXR7 facilitates liver cancer metastasis via epithelial-mesenchymal transition - Guishuai Lv; Yexiong Tan; Hongwei Lv; Tian Fang; Changzheng Wang; Ting Li; Yanting Yu; Congli Hu; Wen Wen; Hongyang Wang; Wen Yang (Science China Life Sciences, 2017)

New Insight into the Effect of Potassium on Commercial SCR Catalyst: Promotion of Thermal Stability - Yanke Yu; Xiaoran Meng; Jinsheng Chen; Jinxiu Wang; Yanting Chen (Water, Air, & Soil Pollution, 2015)